Fatigue during high-intensity endurance exercise: The interaction between metabolic factors and thermal stress - Mitchell, J. B.; Rogers, M. M.; Basset, JT.; Hubing, K. A. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to examine the effects of hot (37° C) and cool (10° C) environments on cycling time to exhaustion (TTE), pH, lactate, and core temperature (Tc). Eleven endurance-trained subjects completed 4 TTE trials: Hot 80% VO2max (H80), Cool 80% (C80), Hot 100% (H100), and Cool 100% VO2max (C100). Esophageal temperature and blood was sampled before, every 5 minutes, at exhaustion, and 3 minutes after exercise and analyzed for lactate, pH, and HCO3-. Multifactorial analysis of variance with repeated measures was used to determine differences between mean values (± SD). Time to exhaustion was shorter in H100 and C100 vs. H80 and C80 (5.64 ± 1.49 minutes, 5.83 ± 1.03 minutes, 12.82 ± 2.0 minutes, and 24.85 ± 6.0 minutes, respectively) and shorter in H80 vs. C80 (p < 0.01). The pH at exhaustion was different among all conditions (7.17 ± 0.06, 7.15 ± 0.07, 7.21 ± 0.04, and 7.24 ± 0.06 units for H100, C100, H80, and C80, respectively, p = 0.02). The Tc at exhaustion was lower in H100 and C100 (37.93 ± 0.67 and 37.62 ± 0.58° C) vs. H80 and C80 (38.54 ± 0.51° C and 38.53 ± 0.38° C) (p < 0.01). In H80 and C80, the higher Tc likely played a greater role in the termination of exercise, whereas, in H100 and C100, pH and metabolic changes may have been more important. Despite these differences, neither an upper limit for Tc nor a lower limit for pH was identified; thus, fatigue based entirely on peripheral factors was not supported, and a combination of peripheral and central processes must be considered. The practical implications of these findings are that aerobic exercise at or near VO2max may be impacted more by metabolic factors, whereas lower intensities (~80% VO2max) may be affected more by heat stress; these differences should be considered when training for events of this type.